The Analysis of Parts of Speech Shift on the Indonesian Translation of Paulo Coelho’s The Alchemist - Sahid Sahid (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2019)
This study aims at analyzing the translation shift which happen in Indonesian translation of Paulo Coelho’s The Alchemist. The researcher focuses on analyzing the parts of speech shift on the process of translation from source language (SL) to target language (TL). Reading for both English text and Indonesian translation are conducted to get the deepest understanding between them. The researcher takes the data randomly and displays the data which is found. The data is then comprehensively analyzed using descriptive qualitative method. The result of this study shows that based on parts of speech shift analysis, it is found that the translator uses that shift (pronoun can be translated into noun, adjective into verb and noun, noun into adjective and verb) to find the equivalence of meaning between source language (SL) to target language (TL).